Perancangan dan Penjadwalan pada Proyek Storage Tank dengan Metode Critical Path Method - Kurniatullah Kurniatullah; Tri Joko Wibowo; Gerry Anugrah Dwiputra (Universitas Serang Raya, 2016)
These companies often experience difficulties caused by unscheduled and planned projects, material delays and lack of workforce for project work. From the problems that occur, this study aims to find activities that are critical trajectories for initial conditions and acceleration based on the Critical Path Method, to determine the difference in processing time from the initial conditions to acceleration conditions and to know the project cost advantages that occur between the initial conditions and conditions acceleration. CPM is a network-based method that uses a balance of time and cost. Each activity can be completed faster than regular time by crossing movements for a certain amount of charges. The method is used to find out when each event will begin and when it will be completed, data retrieval and research conducted. The results of the study showed that critical activity in the initial condition was for 253 days. While the acceleration activities of the total acceleration 208 days with 17 activities entered the critical path, from the results of these calculations the costs obtained from this project for the initial conditions were Rp 1,683,505,000, and the acceleration conditions were Rp 1,734,910,000.